CALCULATION OF THE ECONOMIC ROOF OF THE INTERNAL WATER SUPPLY NETWORK OF THE BUILDING (Modern education and development, 2025)
This article discusses the basics of economic assessment of the internal water supply network of a building. In the design of internal engineering networks, ensuring not only technical, but also economic efficiency is of great importance. The article analyzes the types of investment and operating costs for the water supply system, shows their calculation methods and economic efficiency through practical examples. At the same time, recommendations are given on reducing costs through the use of resource-saving equipment, the selection of modern pipeline materials, and monitoring water consumption. The results of this study are of practical importance for engineers, design organizations, and construction specialists.